2020
DOI: 10.1007/s11625-020-00855-1
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of assessing students’ sustainability competencies: a review of tools

Abstract: While there is growing agreement on the competencies sustainability professionals should possess as well as the pedagogies to develop them, the practice of assessing students' sustainability competencies is still in its infancy. Despite growing interest among researchers, there has not yet been a systematic review of how students' sustainability competencies are currently assessed. This review article responds to this need by examining what tools are currently used for assessing students' sustainability compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 72 publications
2
89
0
3
Order By: Relevance
“…While there is an ample body of theoretical studies on sustainability competency frameworks [40], few discuss the ways in which to evaluate these competencies and/or learning outcomes [41]. The specialised literature focused on learning outcomes uses different terms to refer to the attributes that university students should develop.…”
Section: Evaluating Sustainability Competenciesmentioning
confidence: 99%
See 3 more Smart Citations
“…While there is an ample body of theoretical studies on sustainability competency frameworks [40], few discuss the ways in which to evaluate these competencies and/or learning outcomes [41]. The specialised literature focused on learning outcomes uses different terms to refer to the attributes that university students should develop.…”
Section: Evaluating Sustainability Competenciesmentioning
confidence: 99%
“…Internationally, there is the Sustainability Literacy Test (the SuLiTest) [43] and the Sustainability Consciousness Questionnaire [44], while in Spain we have the Self-perception Skills in Sustainability (SQSS) [45] questionnaire. A literature review of the tools used to evaluate sustainability competencies indicated that, among these tools, there is an overrepresentation of the evaluation methodology based on self-assessment questionnaires [41]. There are certain limitations in the relation of self-assessment with conduct, because of the response bias that self-reported measures surveys may pose [46].…”
Section: Evaluating Sustainability Competenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuing to assess the effect of learning activities and environments that aim to foster learning for sustainability leads to the concept of key sustainability competencies [23]. Several frameworks for sustainability competencies have been presented such as Albareda-Tiana et al's (2020) recent Sustainability Competency Map of Education Degrees [24].…”
Section: Developing a Theoretical Reference Model For Learning And Acmentioning
confidence: 99%